Reformas constitucionais e autonomia municipal no Brasil - Angela Moulin S. Penalva Santos; Liana Portilho Mattos (Economía, Sociedad y Territorio, 2006)
The municipality in Brazil became a federative entity after the Federal Constitution of 1988, within the context of redemocratisation of the power structures, which included the extension of the citizens rights. In this way, the municipal governments became important actors in these policies, having an effect on the relationships between central and local governments, particularly in matters of tax distribution. The increase in financial autonomy of the municipalities diminished the contributions appropriated by the central government, which faced increasing financial obligations due to the extension of the social rights that were introduced by the current Constitution. These facts led the central government to introduce amendments to the Constitution which included an increased taxation not shared with the state and local governments, as well as a transfer of responsibilities, and a greater financial participation, in the public policies.